Determinación de los requerimientos de presión y caudal de vapor para el bloque de potencia de un sistema Fresnel lineal compacto - Dellicompagni, Pablo (2016)
In this paper, the determination of pressure and steam flow required for the generation of electricity by a power block installed in the Linear Fresnel Concentrator (LFC) from the city of San Carlos, Salta is proposed. The steam generated by the LFC has to satisfy certain minimum requirements in terms of quality, pressure, temperature and flow.The determination and calculation of these parameters was performed by testing the electric generator – which will be mounted in San Carlos – in the experimental campus INENCO by a gradual variation of electric power connected. Resistive loads for the determination of the different regimes of rotation on the generator shaft were used.